2015
DOI: 10.1063/1.4908532
|View full text |Cite
|
Sign up to set email alerts
|

Order and correlation contributions to the entropy of hydrophobic solvation

Abstract: The entropy of hydrophobic solvation has been explained as the result of ordered solvation structures, of hydrogen bonds, of the small size of the water molecule, of dispersion forces, and of solvent density fluctuations. We report a new approach to the calculation of the entropy of hydrophobic solvation, along with tests of and comparisons to several other methods. The methods are assessed in the light of the available thermodynamic and spectroscopic information on the effects of temperature on hydrophobic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 65 publications
1
67
0
Order By: Relevance
“…This stabilisation may be quantified by pair correlation functions that contribute to the potential of mean force between each water and the ion, and to the free energy. Recently, we 23 reported derivations for water-water and water-solute pair correlation functions, and found that these correlations can explain the entropy of hydrophobic solvation of small non-polar species in water. This was similar to results obtained by Lazaridis and Paulaitus, 58 who found that the entropy and heat capacities of hydrophobic hydration are well accounted for by solute-water correlations alone.…”
Section: Dipole-ion Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This stabilisation may be quantified by pair correlation functions that contribute to the potential of mean force between each water and the ion, and to the free energy. Recently, we 23 reported derivations for water-water and water-solute pair correlation functions, and found that these correlations can explain the entropy of hydrophobic solvation of small non-polar species in water. This was similar to results obtained by Lazaridis and Paulaitus, 58 who found that the entropy and heat capacities of hydrophobic hydration are well accounted for by solute-water correlations alone.…”
Section: Dipole-ion Correlationsmentioning
confidence: 99%
“…We recently used this method to account for the entropy of hydrophobic solvation. 23 The aim here is to explore the contribution of pair correlations to the solvation free energy of ions in water, and whether a Hofmeister series can be found in these correlations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We approximate the solute cavity as a sphere and assume that the distribution of solvent molecules outside the cavity to be uniform. This first approximation is supported by simulation studies 22 and does not change the dependence of free energy on size. 26 The amount of lost correlation is then a two-body integral, expressed as …”
Section: Theorymentioning
confidence: 72%
“…22 The angular-dependent radial distribution function, g ij , between two dipole moments, l 1 of molecular species i and l 2 of molecular species j separated by r, may be given in terms of the angular dependent PMF as…”
Section: Theorymentioning
confidence: 99%